Endometriosis localized to urinary bladder wall mimicking urinary bladder carcinoma - Mine Genç (Archivio Italiano di Urologia e Andrologia, 2014)
Although endometriosis is a common disease in women of reproductive age, urinary system endometriosis is an exceedingly rare disease that may cause important clinical problems. In this paper we discussed a 42-year-old woman who had urinary bladder endometriosis misdiagnosed as urinary bladder tumor in imaging modalities. The diagnosis of endometriosis was made by histopathological examination of the operative material after partial resection of the urinary bladder. Urinary bladder endometriosis causes nonspecific signs and symptoms in many patients. In female patients presenting with unexplained urinary symptoms the differential diagnosis should include urinary bladder endometriosis that may mimic urinary bladder cancer and lead to difficulties in making definitive preoperative diagnosis.